janeknapp89
janeknapp89
17-09-2017
Mathematics
contestada
3x^2-5x-1 from 8x^2+2x-9
Respuesta :
texaschic101
texaschic101
17-09-2017
8x^2 + 2x - 9 - (3x^2 - 5x - 1) =
8x^2 + 2x - 9 - 3x^2 + 5x + 1 =
5x^2 + 7x - 8 <===
Answer Link
Аноним
Аноним
17-09-2017
[tex](3x^2-5x-1)-(8x^2+2x-9) =3x^2-5x-1-8x^2-2x+9 =3x^2-8x^2-5x-2x-1+9 =-5x^2-7x+8 [/tex]
.
Answer Link
VER TODAS LAS RESPUESTAS ( 17+ )
Otras preguntas
i dont like watching horror movies.They're........There are many ghosts in them
Select the sentence that illustrates the use of proper parallel construction. a. We found the film repulsive, offensive, and we thought it was embarrassing. b.
Two polynomials P and D are given. Use either synthetic or long division to divide P(x) by D(x), and express P in the form P(x) = D(x) · Q(x) + R(x). P(x) = 4x^
Who was the first to jump off the fifty-foot ledge
PLEASE PLEASE HELP!!
(Figure 1) shows the voltage across a 0.10 μF capacitor. Select the correct graph showing the displacement current through the capacitor as a function of time.
Which set of words are closely related to the word onerous? a. view or vision b. rectitude or rectify c. impugn or pungent d. burden or birth
What years did the French & Indian War occur?
why was the man being tortured pit and pendulum
Simplify the following expression 2√2 x √12
ACCESS MORE